P-006 Safety and Efficacy of Endovascular Treatment of Paraophthalmic Internal Carotid Artery Aneurysms. (14th July 2013) - Gaughen, J; Durst, C; Nguyen, Q; Patrie, J; Jensen, M; Evans, A
Abstract : Introduction/Purpose: Within the literature, controversy exists regarding the optimal treatment of ophthalmic segment internal carotid artery aneurysms. The close proximity of the ophthalmic artery and optic nerve increase the complexity of the disease, and the adjacent clinoid process impedes surgical exposure. This study investigates the safety and efficacy of coil embolisation for the treatment of paraophthalmic internal carotid artery aneurysms. Method: A retrospective chart review identified 79 consecutive aneurysms who presented for elective treatment of an ophthalmic artery aneurysm. Patient demographics, details of treatments, effects of treatments, results of follow up procedures, and complications were recorded. Odds ratios were used to measure the effect size. The McNemar Test for systematic discordance was used to test the likelihood of visual improvement or degradation. Results: Primary occlusion rate was 44%. The recurrence rate was 33%. In patients with at least 12 months follow-up, the size of the aneurysm (p=0.016), the size of the aneurysm neck (p=0.028), and hypertension (p=0.03) were predictive of the likelihood of recurrence. There were 3 major complications (4%). The average size of the aneurysm was greater in patients who experienced a major complication, though this did not reach statistical significance due to the low number of complications. 28 (35%) of the 79 patients presented with a visual disturbance that could be attributed to the aneurysm. Visual disturbances were experienced in those patients with larger aneurysms, though this was not statistically significant (p=0.285). Of the 28 patients with visual disturbance, 46% experienced improvement in their symptoms while none of the 51 patients who presented without visual disturbances developed a visual field defect postoperatively (p > 0.001). Conclusion: Endovascular treatment of paraophthalmic internal carotid artery aneurysms appears to be a safe and effective treatment. Major complication rates were found to reside well within the expected rates for intracranial aneurysm treatment. Clinically, almost half of the patients who present with symptomatic visual disturbance or eye pain had significant improvement after treatment, and none of the patients presenting without visual disturbance demonstrated postoperative visual impairment. Disclosures: J. Gaughen: 2; C; Covidien. C. Durst: None. Q. Nguyen: None. J. Patrie: None. M. Jensen: 2; C; Covidien, Microvention, Stryker. A. Evans: 2; C; Covidien, Microvention.